The Integrating Precision Genomic Strategies and Islamic Ethical Perspectives in Stunting Prevention: Focus on the Growth Hormone-IGF-1 Pathway - Qur’ani , Hifdzil; Nisa, Nasywa Khoirun; Pratama, Pramudya; Kasasiah , Ahsanal; Malau, Jekmal (Journal of Pharmaceutical and Sciences, 2026)
Stunting remains one of the major chronic nutritional problems in Indonesia. The national prevalence of stunting has decreased from 37.2% in 2013 to 19.8% in 2024; however, this figure is still above the World Health Organization threshold (<20%) and has not yet reached the national target of 14%. The interaction of nutritional, environmental, and genetic factors influences stunting. Genetic variations within the Growth Hormone–Insulin-like Growth Factor One pathway play a significant role in regulating linear growth in children; disruptions in this pathway can increase vulnerability to stunting. In addition, the majority of Indonesia's population adheres to Islam, making religious values a strategic potential for strengthening health interventions. This review article examines the integration of scientific approaches, focusing on genetics and Islamic values, in stunting prevention by highlighting polymorphisms in the IGF1, IGF1R, and GHR genes and their relevance to the principles of maqāsid al-sharī‘ah, particularly hifz al-nasl (protection of lineage). The analysis is conducted using a descriptive-analytical approach based on recent scientific literature and Islamic references, including the Qur’an, prophetic traditions, and scholarly exegesis. The findings indicate a strong alignment between scientific approaches and Islamic teachings, including the importance of adequate nutrition during pregnancy, exclusive breastfeeding, consumption of lawful, nutritious food, genetic screening efforts consistent with the values of divine decree, and vitamin D supplementation to support Insulin-like Growth Factor One levels. This integration has the potential to enhance community acceptance of stunting-prevention programs, strengthen moral and spiritual motivation, and support the achievement of national stunting-reduction targets. Thus, an approach that combines precise genomics and Islamic values may serve as a contextual and sustainable strategy in shaping a generation that is healthy, intelligent, and spiritually resilient.